Cost–effectiveness of denosumab as a bone protective agent for patients with castration resistant prostate cancer. (2nd January 2016) - Dellis, Athanasios; Papatsoris, Athanasios
Abstract : Fortunately, novel agents are nowadays available for the management of patients with castration-resistant prostate cancer (CRPC). Denosumab is a new bone-protective agent, approved for the prevention and management of skeletal-related events. Studies have demonstrated that denosumab has better efficacy and similar rate of adverse effects in comparison with zoledronic acid, which was the standard bone-protective agent. In the present review we study the cost–effectiveness of denosumab in patients with CRPC.